Do certain surgical steps increase postoperative morbidity after cytoreductive surgery and HIPEC- a retrospective analysis. (December 2022) - Riediger, Carina; Schuster, Tibor; Bork, Ulrich; Schweipert, Johannes; Sigg, Maike; Weiss, Juliane; Weitz, Jürgen
Abstract: Introduction: It has been shown that cytoreductive surgery (CRS) in combination with hyperthermic intraperitoneal chemotherapy (HIPEC) is an effective treatment for patients suffering from peritoneal malignancies. Despite good results, there is an ongoing debate about this treatment due to perioperative morbidity. The aim of this study is to identify relevant risk factors for an unfavorable postoperative outcome after CRS and HIPEC. Materials and methods: A retrospective analysis of a prospectively recorded database of all patients undergoing CRS and HIPEC between 2013 and 2020 in the Department of Surgery of the University Hospital Dresden was performed with a special focus on certain surgical steps of multivisceral resection, one- or 2- stage CRS/HIPEC and underlying diagnosis as possible risk factors for worse postoperative course. Results: N = 173 CRS and HIPEC procedures were performed for various diagnoses. Relevant postoperative morbidity was 24% and 30d-mortality 1.2%. Simultaneous liver resections, preoperative hypalbuminemia and 2-staged CRS/HIPEC were significant risk factors for a worse postoperative course in multivariable analysis. Assessment of the association of simultaneous anastomoses and morbidity and mortality was inconclusive. Conclusion: CRS and HIPEC is a safe treatment without relevant intraoperative morbidity and mortality and acceptable postoperative outcome. One-stage CRS/HIPEC should be preferred. Highlights: CRS and HIPEC is a well-established and safe procedure with favorable outcome for patients. Preoperative measures such as correction of hypalbuminemia and volume management can support the postoperative outcome. Patients receiving simultaneous liver resection as part of cytoreductive surgery should be critically observed. 2-stage CRS/HIPEC should be avoided.